Responsibility beyond growth : a case for responsible stagnation - De Saille, Stevienna; Medvecky, Fabien; Oudheusden, Michael van; Albertson, Kevin; Amanatidou, Effie; Birabi, Timothy; Pansera, Mario (Policy Press scholarship online., 2020)
Critically assessing growth-based models of innovation policy, this book sparks new debate on the role of responsible innovation. Drawing on insights from economics, politics, and science and technology studies, it proposes the concept of 'responsible stagnation' as an expansion of present discussions about growth, responsibility and innovation.